Discovery of a Ce3+-activated red nitride phosphor for high-brightness solid-state lighting. Issue 41 (9th October 2020) - Xia, Yonghui; Li, Shuxing; Zhang, Yingxue; Takeda, Takashi; Hirosaki, Naoto; Xie, Rong-Jun
Abstract : A Ce 3+ -doped red phosphor was screened and developed for high-power solid state lighting. Abstract : Red-emitting phosphors (usually Eu 2+ -activated) play indispensable roles in manipulating the color rendition and color temperature of InGaN-based solid state lighting, but they usually suffer from luminance saturation under high-power density irradiation and thus are hard to use to fabricate high-brightness lighting sources. Ce 3+ -doped red phosphors with short decay times therefore need to be developed to solve the bottleneck problem. In this work, we proposed an empirical structure criterion for screening Ce 3+ -doped red phosphors and discovered HP-CaSiN2 :Ce 3+, which has an emission peak at 610 nm, a full-width at half maximum (FWHM) of 160 nm and a quantum efficiency of 40.3% under 450 nm excitation. Under blue laser irradiation (5.47 W), HP-CaSiN2 :Ce 3+ shows a luminance saturation threshold of 10.89 W mm −2, luminous flux of 1087 lm and luminous efficacy of 198.7 lm W −1, which are 5.4 and 7.3 times higher than the reported CaAlSiN3 :Eu 2+ counterparts. In addition, it can also serve as a red component for creating warm white LEDs with an excellent color-rendering index (Ra) of 91.5 and a small chromaticity shift (Δ E : 1.1 × 10 −2 ). The discovery of the red-emitting HP-CaSiN2 :Ce 3+ makes it possible to search for and design long-wavelength Ce 3+ -doped phosphors by the proposed criterion, and paves an avenue for it to be used in high-power solid state lighting.